Experiments on a crane overspeed protection device. (October 2019) - Zheng, Wei; Zhao, Yongpan; Weng, Yiyong; Duan, Xing; Jin, Haibin
Abstract: A crane overspeed protection device can quickly control the movement of the lifting rope and drum when the load of the crane overspeed, which can prevent the phenomenon that the lifting rope and drum are subjected to gravity and then continue to move under impulse, and effectively improve the braking efficiency of the lifting rope and drum.